2015
DOI: 10.1371/journal.pone.0125780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individualized Centrifugation Training on Orthostatic Tolerance in Men and Women

Abstract: AimsExposure to artificial gravity (AG) at different G loads and durations on human centrifuges has been shown to improve orthostatic tolerance in men. However, the effects on women and of an individual-specific AG training protocol on tolerance are not known.MethodsWe examined the effects of 90 minutes of AG vs. 90 minutes of supine rest on the orthostatic tolerance limit (OTL), using head up tilt and lower body negative pressure until presyncope of 7 men and 5 women. Subjects were placed in the centrifuge na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…Furthermore, due to small sample size, the gender effect on blood pressure regulation and alteration in the dynamics of such behavior under artificial hypergravity remains to be understood. Female astronauts account for approximately 22% of total astronaut population ( Harm et al, 2001 ), and studies have demonstrated significant gender difference in autonomic mechanisms leading to stable stance and in response to countermeasures designed to mitigate deleterious effect of spaceflight deconditioning ( Arzeno et al, 2013 ; Goswami et al, 2015b ; Hughson et al, 2016 ; Macaulay et al, 2016 ). Therefore, generalization of gender effect would further improve our understanding regarding the potential of SAHC as a training tool toward evoking blood pressure regulatory controls analogous to standing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to small sample size, the gender effect on blood pressure regulation and alteration in the dynamics of such behavior under artificial hypergravity remains to be understood. Female astronauts account for approximately 22% of total astronaut population ( Harm et al, 2001 ), and studies have demonstrated significant gender difference in autonomic mechanisms leading to stable stance and in response to countermeasures designed to mitigate deleterious effect of spaceflight deconditioning ( Arzeno et al, 2013 ; Goswami et al, 2015b ; Hughson et al, 2016 ; Macaulay et al, 2016 ). Therefore, generalization of gender effect would further improve our understanding regarding the potential of SAHC as a training tool toward evoking blood pressure regulatory controls analogous to standing.…”
Section: Discussionmentioning
confidence: 99%
“…If any subject developed presyncope the experiment was terminated immediately. Presyncope was defined as [ 26 , 27 ] : blood pressure dropping below 80 mm Hg or by ≥20 mm Hg/minute; diastolic by ≥10 mm Hg/minute; and/or HR decreasing by ≥15 bpm. Additionally subjects were instructed to avoid any unnecessary movements, remain as still as possible and breathe normally at all times.…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence from studies of ambulatory and deconditioned men and women indicate that 90 min of an individualized short-arm centrifuge AG profile significantly increases participants’ orthostatic tolerance limits via increased blood pressure and cerebral blood flow (Goswami et al 2015a, b; Evans et al 2015). However, men and women respond differently to these stressors (Harm et al 2001).…”
Section: Introductionmentioning
confidence: 99%